Kinetic Modeling of the Arabidopsis Cryptochrome Photocycle: FADHo Accumulation Correlates with Biological Activity - Procopio, Maria; Link, Justin; Engle, Dorothy; Witczak, Jacques; Ritz, Thorsten; Ahmad, Margaret (Frontiers in Plant Science, 2016)
Cryptochromes are flavoprotein photoreceptors with multiple signaling roles during plant de-etiolation and development. Arabidopsis cryptochromes (cry1 and cry2) absorb light through an oxidized flavin (FADox) cofactor which undergoes reduction to both FADH° and FADH– redox states. Since the FADH° redox state has been linked to biological activity, it is important to estimate its concentration formed upon illumination in vivo. Here we model the photocycle of isolated cry1 and cry2 proteins with a three-state kinetic model. Our model fits the experimental data for flavin photoconversion in vitro for both cry1 and cry2, providing calculated quantum yields which are significantly lower in cry1 than for cry2. The model was applied to the cryptochrome photocycle in vivo using biological activity in plants as a readout for FADH° concentration. The fit to the in vivo data provided quantum yields for cry1 and cry2 flavin reduction similar to those obtained in vitro, with decreased cry1 quantum yield as compared to cry2. These results validate our assumption that FADH° concentration correlates with biological activity. This is the first reported attempt at kinetic modeling of the cryptochrome photocycle in relation to macroscopic signaling events in vivo, and thereby provides a theoretical framework to the components of the photocycle that are necessary for cryptochrome response to environmental signals.